WRIPUB 2022
DOI: 10.46830/wrirpt.22.00043
|View full text |Cite
|
Sign up to set email alerts
|

The State of Nationally Determined Contributions: 2022

Abstract: This report takes stock of countries’ latest NDCs and examines how these commitments have evolved since the Paris Agreement entered into force, identifying overall trends and pinpointing the elements where further action is needed. It finds that countries are making incremental progress on strengthening their NDCs, but what we really need to achieve the goals of the Paris Agreement is urgent transformational change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Most of the new categories are located at levels 3 and 4 of the taxonomy trees (as presented in Appendix A). Research has shown that the more specific and detailed the measures for coping with risk, the greater the control and understanding of the risk (as described in [1,34,35]). It is noteworthy that the new taxonomy includes new categories, and some categories have been removed compared to Boutang The taxonomy has evolved between the two NDC editions in terms of project categories.…”
Section: Comparison Of Fitness Coefficient Values Between Two Edition...mentioning
confidence: 99%
“…Most of the new categories are located at levels 3 and 4 of the taxonomy trees (as presented in Appendix A). Research has shown that the more specific and detailed the measures for coping with risk, the greater the control and understanding of the risk (as described in [1,34,35]). It is noteworthy that the new taxonomy includes new categories, and some categories have been removed compared to Boutang The taxonomy has evolved between the two NDC editions in terms of project categories.…”
Section: Comparison Of Fitness Coefficient Values Between Two Edition...mentioning
confidence: 99%
“…It has been acknowledged that the "Avoid-Shift-Improve" approach is strategic to achieve net-zero carbon by 2050 under the 2015 Paris Agreement [3][4][5]. This holistic approach is focused on (i) "avoiding" unnecessary travel needs through urban redesign, (ii) "shifting" to sustainable transport modes, and (iii) "improving" the travel experience of sustainable modes [5][6][7][8]. The superblock model integrates "avoid" and "shift" strategies by reclaiming public space and promoting sustainable mobility [9].…”
Section: Introduction 1introduction To Superblocks and Their Analysismentioning
confidence: 99%
“…and two open-source tools (Climate Action Tracker 2023a;Fransen et al 2022, as updated using Climate Watch 2023. mitigation 1Second, the number of NDCs noting that they may use international market mechanisms to achieve their targets has increased to 121, up from 92 at COP 21. Article 6 of the Paris Agreement provides that parties may cooperate with other parties to achieve their targets by trading emissions credits or offsets.…”
mentioning
confidence: 99%